Morphological and Trichome Characteristics of Pyrrosia (Polypodiaceae) at Andalas University - Audina, Zikkra; Mildawati, Mildawati; Mairawita, Mairawita (Jurnal Biologi Tropis, 2025)
Pteridophyta, a group of vascular cryptogams, demonstrate remarkable adaptability to a wide range of environmental conditions. Within this group, the genus Pyrrosia (Polypodiaceae) is particularly notable for its unique morphological adaptations and the presence of trichomes key features in taxonomic identification and species delimitation. This study investigates the morphological characteristics and trichome structures of Pyrrosia species growing in the vicinity of Andalas University, West Sumatra, Indonesia. Field sampling was conducted through systematic exploration in the Biological Garden of the Faculty of Mathematics and Natural Sciences, Andalas University. Specimens were collected and examined using a binocular light microscope (Sinher XSZ-107) to observe the morphology of primary vegetative organs roots, rhizomes, and leaves as well as trichome characteristics on the leaf surface. Three Pyrrosia species were identified: P. angustata, P. piloselloides, and P. adnascens. Distinct morphological differences were observed among them. The sterile leaves of P. angustata are lanceolate, while those of P. piloselloides and P. adnascens are oblong. The fertile leaves also vary: lanceolate in P. angustata, elliptical in P. piloselloides, and narrowly pointed in P. adnascens. A consistent feature across all three species is the presence of stellate (star-shaped) trichomes, a characteristic of taxonomic significance within the genus. The findings of this study contribute to a better understanding of morphological variation within Pyrrosia and reinforce the importance of micromorphological traits, particularly trichomes, in supporting species identification and classification within the Polypodiaceae.